2011
DOI: 10.1364/aop.3.000161
|View full text |Cite
|
Sign up to set email alerts
|

Orbital angular momentum: origins, behavior and applications

Abstract: As they travel through space, some light beams rotate. Such light beams have angular momentum. There are two particularly important ways in which a light beam can rotate: if every polarization vector rotates, the light has spin; if the phase structure rotates, the light has orbital angular momentum (OAM), which can be many times greater than the spin. Only in the past 20 years has it been realized that beams carrying OAM, which have an optical vortex along the axis, can be easily made in the laboratory. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
1,612
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,809 publications
(1,626 citation statements)
references
References 185 publications
6
1,612
1
7
Order By: Relevance
“…Both components are circularly polarized but, while the B 0 component is in phase with the input beam, the B 1 component is in counter-phase and possesses an azimuthal phase e iϕ associated to beams carrying ± orbital angular momentum (OAM) per photon [132][133][134][135]. In other words, every point of the B 1 component is circularly polarized but there is a rotation of the field by 2π on running along the azimuthal angle ϕ.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Both components are circularly polarized but, while the B 0 component is in phase with the input beam, the B 1 component is in counter-phase and possesses an azimuthal phase e iϕ associated to beams carrying ± orbital angular momentum (OAM) per photon [132][133][134][135]. In other words, every point of the B 1 component is circularly polarized but there is a rotation of the field by 2π on running along the azimuthal angle ϕ.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…8 Searches for transfer of OAM to atomic and molecular systems have as yet yielded no measurable results. 9 Qualitatively, one might expect efficient OAM coupling to a target only when the target's spatial scale is comparable to that of spatial variations in the intensity pattern of the laser beam associated with the OAM, i.e., the target must be big enough to "sense" that it is in a beam with OAM. In our case, we used beams with Laguerre-Gaussian (LG) modes whose field amplitude is the complex scalar function: 1…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…[6] It has been shown that plasmonic nanostructures forming 1D [7] elements, 2D metasurfaces, [8][9][10] and 3D metamaterials [11] can exhibit linear chiral response due to their own, intrinsic chirality. Also semiconductor nanostructures can exhibit chiral features.…”
mentioning
confidence: 99%